The Threepenny Opera: a learning play in a laboratory of a late Soviet school - Volkova, Viktoria (Revista Brasileira de Estudos da Presença, 2021)
This article presents a case study considering key scenes from Bertolt Brecht’s play The Threepenny Opera that were performed in a Moscow school theatre of the late USSR, in 1982. Collective working under the conditions of a theatre laboratory engendered a new methodological approach referring to another Brechtian format, namely, the learning play. The article problematizes the self-reflective learning of the students and their teacher whilst working under theatre laboratory conditions on a Brechtian text. The self-reflective practices were discovered by the amateur actors through the sudden but inevitable effect of Brecht’s alienation technique within the emerging learning play format.